GEODYNAMIC PROBLEMS OF THE JUNCTION BETWEEN THE AGIN AND ARGUN ZONES OF TRANSBAIKALIA: EVIDENCE FROM U-PB SHRIMP DATING OF ROCKS OF THE TSUGOL GABBRO-PLAGIOGRANITE MASSIF - Lykhin D.A.; Presnyakov S.L.; Nekrasov G.E.; Ruzhentsev S.V.; Golionko B.G.; Balashova Yu.S. (My University, 2007)
The geodynamics of the junction of the Mongol–Okhotsk belt and Argun–Mamyn (Amur) continental massif is one of the key and least developed problems of Transbaikalia because of the relatively poor age constraints of magmatic complexes formed during tectonic interaction of these domains in the Precambrian and Paleozoic. Our data on the Tsugol Massif shed light on this problem.